2017
DOI: 10.1002/pc.24537
|View full text |Cite
|
Sign up to set email alerts
|

Creep and interfacial behavior of carbon fiber reinforced epoxy filament wound laminates

Abstract: This article focuses on the investigation of the interfacial and creep characteristics of carbon fiber‐reinforced epoxy laminates at different fiber orientations. Flat unidirectional 12‐layer laminates were manufactured by dry‐filament winding and cured under hot compression. The following winding sequences were studied: [0]12, [30]12, [45]12, [60]12, and [90]12. Short‐beam testing aided by microscopy and dynamic mechanical analysis were used to assess interfacial characteristics and creep behavior of the lami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 31 publications
(45 reference statements)
0
29
0
1
Order By: Relevance
“…Discrepancies presented on dynamic-mechanical results were associated to the matrix/ fiber interface, since resin, fiber volume and orientation were similar. In similar study, Almeida Jr. et al 11 analyzed the creep and interfacial behavior of carbon fiber reinforced epoxy filament wound laminates at five different winding sequences. The authors used two different analytical models for it (Findley and Burger's models).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discrepancies presented on dynamic-mechanical results were associated to the matrix/ fiber interface, since resin, fiber volume and orientation were similar. In similar study, Almeida Jr. et al 11 analyzed the creep and interfacial behavior of carbon fiber reinforced epoxy filament wound laminates at five different winding sequences. The authors used two different analytical models for it (Findley and Burger's models).…”
Section: Introductionmentioning
confidence: 99%
“…The present study has as novelty a detailed structureproperty relationship study on viscoelastic properties of carbon NCF/epoxy composites molded by VARTM. The viscoelastic properties of the composite were evaluated by dynamic mechanical analysis and by Findley, Burgers and Weibull model parameters using creep testing based on literature [11][12][13][14] . Different conditions of temperature and static stress were selected aiming to evaluate the behavior along time on creep tests.…”
Section: Introductionmentioning
confidence: 99%
“…This parameter is temperature-dependent because the bulk material tends to become softer with temperature, which decreases the instantaneous modulus (Fancey 2005;Xu et al 2010;Yang et al 2006aYang et al , 2006b). This parameter can be associated with the storage modulus in the glassy region, where higher temperatures decrease the modulus when compared to the same static stress applied (Almeida et al 2018a(Almeida et al , 2018b. These results suggest that it is difficult to have some viscous flow on the bulk material due to a higher elastic deformation at a short-time response.…”
Section: Resultsmentioning
confidence: 94%
“…Significant progress has been carried out in terms of the time-independent behavior of CFRP composites. However, in engineering applications, compliance and deformation properties are stress-and time-dependent (Almeida et al 2018a(Almeida et al , 2018bOrnaghi et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the creep behavior, the Findley power law model is one of the most widely used to describe this phenomenon in composite materials and has been recommended, inclusively, by the ASCE Structural Plastics Design Manual to analyze and design the long-term strength [ 50 ]. The Findley’s power law is given by Equation (5): where ε ( t ) is the creep displacement at time t , ε 0 is the instantaneous elastic displacement or time-independent, A is the amplitude of transient creep (time-dependent), and n is a constant independent of the stress and generally less than one [ 51 ]. Several studies can be found in the open literature, where the Findley’s power law was also applied to short-term creep data [ 27 , 28 , 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%